ANALYSIS OF BEKASI CITY REGIONAL REGULATION NUMBER 4 OF 2023 CONCERNING WOMEN'S EMPOWERMENT AND PROTECTION - Siregar, Nazuwa Irbah Siregar; Aminulloh, Muhammad (DE'RECHTSSTAAT, 2024)
Regional Regulation of Bekasi City Number 4 of 2023 concerning Women's Empowerment and Protection is an important step in realizing gender equality and justice for women in Bekasi City. The aim of this research is to determine the implementation of Bogor Regency regional regulation number 4 of 2023 concerning the protection of women. This analysis will be carried out using normative and empirical legal research methods. The result of this reseach find Bekasi City Regulation Number 4 of 2023 concerning Women's Empowerment and Protection is an important legal instrument to realize gender equality and protect women's rights in Bekasi City. This Regional Regulation provides a strong foundation for implementing various programs and activities aimed at empowering and protecting women. It is hoped that this new Regional Regulation can be an effective instrument to realize gender equality and justice for women and children in Bekasi City. It is important to remember that this analysis is based only on the text of the new Regional Regulation and information available to the public. To obtain a more in-depth analysis, further research and more complete data collection are needed.